11β-HSD1 Inhibitors for the Treatment of Type 2 Diabetes and Cardiovascular Disease - Anderson, Anna; Walker, Brian R. (Drugs (New York, N.Y.), 2013)
Inhibition of the enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) has been proposed as a novel therapeutic target for the treatment of type 2 diabetes mellitus. Over 170 new compounds targeting 11β-HSD1 have been developed. This article reviews the current published literature on compounds that have reached phase II clinical trials in patients with type 2 diabetes, and summarises the preclinical evidence that such agents may be useful for associated conditions, including peripheral vascular disease, coronary artery disease and cognitive decline. In clinical trials, 11β-HSD1 inhibitors have been well tolerated and have improved glycaemic control, lipid profile and blood pressure, and induced modest weight loss. The magnitude of the effects are small relative to other agents, so that further development of 11β-HSD1 inhibitors for the primary therapeutic indication of type 2 diabetes has stalled. Ongoing programmes are focused on additional benefits for cognitive function and other cardiovascular risk factors.